Circulating Nuclear Factor-Kappa B Mediates Cancer-Associated Inflammation in Human Breast and Colon Cancer: Nuclear factor-kappa B in breast and colon cancer - Uzun, Hafize; Kundaktepe, Berrin Papila; Sozer, Volkan; Kocael, Pinar; Durmus, Sinem; Kurtulus, Dilara; Papila, Cigdem; Gelisgen, Remise (Journal of Medical Biochemistry, 2020)
Background: Inflammation is recognized as a hallmark feature of cancer development and progression. The aim of our study was to investigate the significance of serum nuclear factor kappa-B (NF-кB) levels as a circulating marker in the monitor of inflammation in breast and colon cancer; to show the relationship between NF-кB with inflammatory parameters as tumor necros faktor-α (TNF-α), soluble TNF-related apoptosis inducing ligand (sTRAIL), interleukin-6 (IL-6), pentraxin-3 (PTX-3), procalcitonin (PCT), and C-reactive protein (CRP) levels. Methods: Serum NF-кB, TNF-α, sTRAIL, IL-6, PTX-3, PCT, and serum CRP levels were measured using enzyme linked immunosorbent assay (ELISA) in 40 patients with breast cancer, 40 patients with colon cancer and 30 healthy controls. Results: The serum NF-кB, TNF-α, IL-6, PTX-3, PCT and serum CRP concentration was significantly higher and the serum sTRAIL concentration was significantly lower in patients with breast and colon cancer than in those with an healthy controls. NF-кB were positive correlated with CRP and negative corelated with sTRAIL. Conclusions: These results suggest that increased NF-кB may decrease the clinical efficacy of sTRAIL in solid tumour cells. There is relationship between inflammation and carcinogenesis so that the development of cancer occurs with chronic inflammation in breast and colon. The study results have shown that colon and breast cancer patients have increased systemic inflammation, as measured by increased circulating cytokines, and acute phase proteins, or by abnormalities in circulating cells. NF-кB may combine with other markers of the systemic inflammatory response in prognostic scores in cancer. In addition to surgical resection of the tumor, conventional radio- and chemotherapy for cancer treatment, the use of sTRAIL or other agonists for cancer therapy appeared a new potential therapy.